Socjologia rodziny – Ja, My i Oni - Singly, François de (Instytut Socjologii Uniwersytetu Wrocławskiego, 2020)
According to Norbert Elias, the concept of “the society of individuals” is what characterises contemporary European societies, whereby individuals self-define first in terms of special features and only then through a sense of belonging to a group. ‘Me’ overtakes ‘us’. It is from this perspective that the article looks at the process of individualisation that takes place within family. It describes changes connected with the intersection of the process of individualisation with conjugal relationships and relationships between parents and children.
Keywords: men; ethnocultural inequality; social norms; subjectivity; autonomy; action; appreciation; youth; intersectionality; paternity; living-apart-together relationships; memes; family; maternity; mixed marriages; individualization; parenthood; deviation; social disapproval; couple; culture; normative transgression; conjugal system; pandemic COVID-19; trust; communication; interactive rituals; love; missing persons; artistic success and failure; sexuality; Internet; quarantine; multiple parenthood; social circles; social exclusion; careers of smokers; gender; self-esteem; emotions; art field